Analysis of the Use of Information Media on the Performance of Pasmar Soldiers 1 - Tegar , Hayat; Firdaus, Firdaus; Hardiman, Hardiman (JURNAL EKBIS, 2023)
The purpose of this study is to analyze and prove the effect of using Smartphones on the performance of Pasmar 1 soldiers. To analyze and prove whether the use of Smartphones can improve the performance of Pasmar 1 soldiers. simple linear regression. The research population is in Pasmar 1, both those with the rank of officer, non-commissioned officer and enlisted, totaling 1708 personnel, with the slovin formula the sample in this study amounted to 235 Pasmar 1 soldiers who will be sampled. The results of the analysis show that partially the variable use of Smartphone (X) has a positive and significant effect on the Performance of Pasmar 1 Soldiers (Y). This shows that the application of the use of smartphone technology will greatly contribute strongly to the performance of Pasmar 1 soldiers.